2015
DOI: 10.3346/jkms.2015.30.8.1092
|View full text |Cite
|
Sign up to set email alerts
|

Routine Screening and Consultation Facilitate Improvement of Metabolic Syndrome

Abstract: This randomized controlled trial study aimed to investigate the effects of a lifestyle intervention on metabolic syndrome (MetS) among middle-aged Koreans. A total of 243 middle-aged Koreans with MetS were randomly assigned to either of 2 types of lifestyle intervention for MetS and followed for 12 months. Health examinations and interventions were implemented at 16 regional branch facilities of a Korean medical institution from 2010, following the NCEP-ATP III criteria and recommendations. Lifestyle intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Considering the results of a number of lifestyle modification interventions, the absolute reduction in MetS prevalence following substantial smoking cessation is expected to be no less than 15%. [24][25][26][27][28] The main prespecified secondary endpoint is an absolute change in the sum of the individual factors of the MetS (as defined by NCEP criteria) measured at each study time point (between and within study groups). Other secondary endpoints include change in each individual factor of the MetS (as defined by NCEP criteria) measured at each study time point (between and within study groups) and change of the variables given in table 1B measured at each study time point (between and within study groups).…”
Section: Objectives and Endpointsmentioning
confidence: 99%
“…Considering the results of a number of lifestyle modification interventions, the absolute reduction in MetS prevalence following substantial smoking cessation is expected to be no less than 15%. [24][25][26][27][28] The main prespecified secondary endpoint is an absolute change in the sum of the individual factors of the MetS (as defined by NCEP criteria) measured at each study time point (between and within study groups). Other secondary endpoints include change in each individual factor of the MetS (as defined by NCEP criteria) measured at each study time point (between and within study groups) and change of the variables given in table 1B measured at each study time point (between and within study groups).…”
Section: Objectives and Endpointsmentioning
confidence: 99%
“…Blood cholesterol levels were not significantly improved by the devised program. N.-H. Yoo et al (2015) demonstrated that a 12-week multi-component lifestyle intervention program effectively reduced serum triglyceride levels but did not increase HDL-cholesterol levels in patients with metabolic syndrome. van Namen et al ( 2019) conducted a metaanalysis and reported that lifestyle modification interventions can reduce serum triglyceride levels, but do not increase HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…This was a secondary analysis of a previous clinical trial study which explored the effectiveness of dietary counseling [22]. The primary study, which provided the data, is registered in the Clinical Research Information Service by Korea Centers for Diseases Control and Prevention, Republic of Korea (registration number: KCT0000275 and KCT 0000446).…”
Section: Methodsmentioning
confidence: 99%